Climate Vulnerability and Cardiovascular‐Kidney‐Metabolic Disease in the United States - Pedro Rafael Vieira de Oliveira Salerno; P. Grace Tee Lewis; Zhuo Chen; Jean‐Eudes Dazard; Sarju Ganatra; Eman Nayaz Ahmed; Khurram Nasir; Salil V. Deo; Sanjay Rajagopalan; Sadeer Al‐Kindi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background There is an incomplete understanding of the impact of climate change on cardiovascular‐kidney‐metabolic (CKM) syndrome. Although climate change affects all Americans, certain communities and individuals may suffer a disproportionate burden. Therefore, this study's objective was to explore the relationship between the Climate Vulnerability Index domains and the prevalence of CKM components in the United States. Methods This cross‐sectional study obtained health outcomes from Centers for Disease Control and Prevention Population Level Analysis and Community Estimates (2021) and assessed the census tract‐level prevalence of coronary heart disease, chronic kidney disease, obesity, diabetes, dyslipidemia, and hypertension. ANOVA was used to assess statistically significant differences in the means of CKM components between quartiles of each climate change domain. Linear regression models assessed the association between each domain and outcome, followed by models adjusted by baseline Climate Vulnerability Index components. Fully adjusted models included all 3 climate change domains and the baseline Climate Vulnerability Index components. Results Data for 70 300 census tracts, covering 299.8 million individuals, were included. Statistically significant differences (P<0.001) in CKM prevalence were found between quartiles of all climate change domains. These associations persisted after adjusting for baseline domains (environment, social/economic, and infrastructure) and in the full model including all domains. Conclusions The Climate Vulnerability Index's climate change component was associated with the prevalence of CKM components (coronary heart disease, chronic kidney disease, obesity, diabetes, dyslipidemia, and hypertension). These findings suggest that populations with CKM may be associated with increased climate vulnerability, underscoring the need for a deeper understanding of climate change as a determinant of health.